Implementasi Pendidikan Kewirausahaan dan Bimbingan Teknis Pada Pertumbuhan Kredit Usaha Produktif di KSP CU Bathera Sejahtera Maumere - Jelita, Sofiana; Rangga, Yoseph Darius Purnama; Gula, Valeria Eldyn (Universitas Nusa Nipa Maumere, 2026)
The Merdeka Belajar Kampus Merdeka (MBKM) program through internship activities provides opportunities for students to be directly involved in the professional world and community service. This study aims to analyze the role of entrepreneurship education and productive business mentoring implemented by KSP CU Bathera Sejahtera Maumere in improving the business capacity of its members. The research employed a descriptive qualitative approach, with data collected through observation, interviews, and documentation during the internship program. The results indicate that entrepreneurship education and productive business mentoring make a positive contribution to enhancing entrepreneurial knowledge, financial management, and business sustainability among cooperative members. Therefore, structured and continuous mentoring programs need to be further developed to strengthen the economic independence of cooperative members.